Acupuncture improves the residual urine volume of bladder of middle age patients with urinary retention post-stroke: A protocol for systematic review and meta analysis. Issue 47 (25th November 2022) - Cao, Di; Yang, Qiguang; Qi, Fengjun; Gu, Shuhong; Yu, Tao; Zhu, Lin; Liu, YiMing; Gui, Junjing; Yang, Baoru; Zhang, Xiaolin
Abstract : Background: There are 15 million new cases of stroke every year in the world, 65% of which have dysuria in the early stage of stroke, which seriously affects the quality of life of stroke patients. The purpose of this study is to evaluate the results of randomized controlled trials to determine whether acupuncture can improve the residual urine volume of the bladder in middle age patients with urinary retention post-stroke. Methods: Eight databases, including China National Knowledge Infrastructure, Chinese Scientific Journal Database, Cochrane Central Register of Controlled Trials, Embase, MEDLINE, PubMed, Wanfang Database, and Web of Science, will be searched using English and Chinese search strategies. In addition, manual retrieval of research papers, conference papers, ongoing experiments, internal reports, etc, will supplement electronic retrieval. All eligible studies published on or before October 1, 2022 will be selected. To enhance the effectiveness of the study, only clinical randomized controlled trials related to the use of manual acupuncture for the treatment of urinary retention post-stroke will be included. Conclusion: The residual urine volume of bladder will be the primary outcome measure, whereas the Clinical efficiency will be the secondary outcomes. Side effects and adverse events will be included as safety evaluations. To ensure the quality of the systematic evaluation, study selection, data extraction, and quality assessment will be independently performed by two authors, whereas a third author will resolve any disagreement.